AKRB POLA KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI DINAS KOMUNIKASI INFORMATIKA DAN PERSANDIAN KOTA YOGYAKARTA - Ajeng Pratiwi Defitri; Ardiyanto Wardhana (Jurnal Ilmu Komunikasi AKRAB, 2024)
ABSTRACTCommunication is one of the most important aspects in life. Communicationactivities include conveying and receiving information, ideas and feedback. In anorganization, communication plays a role in uniting the interests of all members to achieve acommon goal. Communication is the "soul" of an organization. Therefore, thecommunication patterns formed in an organization become the existence of the organizationitself. The Yogyakarta City Communication, Informatics and Cryptography Department(Diskominfosan) has experienced improved performance in the last three years and is stillworking on the problems they encountered in achieving performance in 2022. This researchfocuses on how communication patterns occur at the Yogyakarta City Diskominfosan inoptimizing performance and dealing with problems that occur. This research uses descriptivequalitative methods with data collection techniques of observation, interviews anddocumentation. Interviews are an initial strategy to find out communication patterns carriedout by the Yogyakarta City Information and Coding Communication Service. The results ofthe research show that the communication patterns used by the Yogyakarta City Informationand Coding Communication Service are wheel communication patterns, circlecommunication patterns and all-channel communication patterns. The communication flowused is top-down communication, for example in instructing the implementation of workorders and providing motivation. Bottom-up communication in the form of ideas or inputfrom employees. Horizontal communication takes the form of work meetings andcollaboration between fields. Then there are four approaches taken, namely the scientificapproach, the human relations approach, the systemic approach and the cultural approach.The supporting factors for communication in the organization of the Yogyakarta CityInformation Communication and Encryption Service include supporting communication tools,understanding the situation and conditions, openness, facilities, motivation andappreciation.Keywords: Communication Patterns, Organization, Performance, Yogyakarta CityCommunication, Informatics and Coding Department.